2019
DOI: 10.3390/cancers11111635
|View full text |Cite
|
Sign up to set email alerts
|

SLUG Directs the Precursor State of Human Brain Tumor Stem Cells

Abstract: In glioblastoma (GBM), brain tumor stem cells (BTSCs) encompass heterogenous populations of multipotent, self-renewing, and tumorigenic cells, which have been proposed to be at the root of therapeutic resistance and recurrence. While the functional significance of BTSC heterogeneity remains to be fully determined, we previously distinguished relatively quiescent stem-like precursor state from the more aggressive progenitor-like precursor state. In the present study, we hypothesized that progenitor-like BTSCs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Consistent observations have been made in breast cancer and prostate cancer, where SLUG degradation promotes the differentiation of breast cancer stem cells [Fraile et al, 2020], and the basal prostate cells that expressed SLUG exhibited a partial EMT phenotype and displayed increased stemness ability [Kahonouva et al, 2020]. The functional contribution of SLUG in vitro and/or in vivo enabling stemness is also observed in human epidermal progenitor cells [Mistry et al, 2014] as well as other cancers such as glioblastoma [Chesnelong et al, 2019], hepatocellular carcinoma [Tang et al, 2016;Sun et al, 2014], colorectal cancer [Kato et al, 2020], lung cancer [Kim et al, 2020] and squamous cell carcinomas [Yu et al, 2016;Moon et al, 2020]. Whether higher stemness is connected to a hybrid E/M phenotype in these cancers remains to be identified.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Consistent observations have been made in breast cancer and prostate cancer, where SLUG degradation promotes the differentiation of breast cancer stem cells [Fraile et al, 2020], and the basal prostate cells that expressed SLUG exhibited a partial EMT phenotype and displayed increased stemness ability [Kahonouva et al, 2020]. The functional contribution of SLUG in vitro and/or in vivo enabling stemness is also observed in human epidermal progenitor cells [Mistry et al, 2014] as well as other cancers such as glioblastoma [Chesnelong et al, 2019], hepatocellular carcinoma [Tang et al, 2016;Sun et al, 2014], colorectal cancer [Kato et al, 2020], lung cancer [Kim et al, 2020] and squamous cell carcinomas [Yu et al, 2016;Moon et al, 2020]. Whether higher stemness is connected to a hybrid E/M phenotype in these cancers remains to be identified.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, SLUG and SNAIL have been reported to inhibit each other in oral cancer [Nakamura et al, 2018] and breast cancer [Ganesan et al, 2015]. The effect of SLUG on EMP dynamics can also be influenced by upstream regulators of SLUG such as RNF8, YAP, C/EBPδ, miR-151, CBP, RCP, HDAC1, HDAC3, BRD4 and STAT3 [Cheng et al, 2020;Chesnelong et al, 2019;Kuang et al, 2020;Wang et al, 2020;Daugaard et al, 2017;Jury et al, 2020;Dai et al, 2020;Hwang et al, 2017;Hu et al, 2020;Shafran et al, 2020]. Moreover, SLUG may be involved in feedback loops with one or more p63 isoforms [Srivastava et al, 2018;Dang et al, 2016;Herfs et al, 2010] that can also enable a partial EMT [Jolly et al, 2017a;Westcott et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Chesnelong et al reported that the progenitor-like GSCs with mesenchymal features arise in a STAT3-dependent manner. [54] Mechanistically, STAT3 can modulate the activity of SLUG, inducing mesenchymal transformation, while progenitor-like GSCs acquire more aggressive phenotype. [54] In line with this work, STAT3/SLUG axis can induce mesenchymal transformation in irradiated/invasive patient-derived GSCs.…”
Section: Core Transcriptional Regulatorsmentioning
confidence: 99%
“…[ 54 ] Mechanistically, STAT3 can modulate the activity of SLUG, inducing mesenchymal transformation, while progenitor‐like GSCs acquire more aggressive phenotype. [ 54 ] In line with this work, STAT3/SLUG axis can induce mesenchymal transformation in irradiated/invasive patient‐derived GSCs. [ 55 ] Moreover, addition of AZD1480 (a STAT3 inhibitor) to radiation therapy leads to an effective reduction of tumor burden in mice PN xenograft models.…”
Section: Molecular Mechanisms Of Mesenchymal Transformation In Gbmmentioning
confidence: 99%
“…TICs and TPCs in EMT-induced quiescence are highly resistant to chemotherapy, presumably because these carcinoma cells are highly plastic [ 55 , 56 , 57 ]. For instance, NOTCH4, which is highly expressed in triple-negative breast carcinoma (TNBC), contributes to EMT and maintains the cells in a mesenchymal-like state through an upregulation of SNAI2 and GAS1 [ 58 ].…”
Section: Carcinoma Cell Plasticity Contributes To Therapy Evasion and Stemnessmentioning
confidence: 99%